Assessment of the revised implementing guidelines on the operation and management of school canteens in public secondary schools in the division of Laguna : basis for enhancement program - Alonte, Lani A. (Manila : National University, 2015)
The students' populace in general would be getting the most benefit because improvements made at the school canteen and its operation would be directed or geared for their welfare. Changes on its management and operation will have a great impact on students who are the primary clientele of the school canteen.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.